Evaluation of Changes in the Quality of Life of Patients with Peripheral Arterial Disease (PAD) Following Successful Revascularization Using Endovascular Techniques with the Vascular Quality of Life Questionnaire-6 (Vascuqol-6) at Dr. Cipto Mangunkusumo National General Hospital - Defri Heryadi; Dedy Pratama; Wawan Mulyawan (Green Publisher Indonesia, 2026)
Background: Peripheral arterial disease (PAD) is a chronic vascular disease that significantly affects physical function and quality of life. Endovascular revascularization is a primary treatment modality for symptomatic PAD; however, evaluation of its success should include patient-reported outcomes, such as quality of life. This study aimed to evaluate changes in quality of life among patients with PAD after endovascular revascularization using the VascuQoL-6 instrument. Methods: This was an analytic observational study with a pre–post design involving patients with PAD who underwent endovascular revascularization at Dr. Cipto Mangunkusumo National General Hospital. Quality of life was assessed using the VascuQoL-6 before and one month after the procedure. Changes in scores were analyzed using paired comparative tests. Results: A total of 32 patients were enrolled in this study. The mean ankle-brachial index (ABI) increased after endovascular revascularization compared with before the procedure. The median total VascuQoL-6 score increased significantly after the procedure, with all patients showing improvements in quality of life. Improvements occurred across all quality-of-life domains, with the greatest improvements observed in the activity and pain domains. Conclusion: Endovascular revascularization effectively improved the quality of life of patients with PAD based on the VascuQoL-6 instrument, particularly in the activity and pain domains.